CHEMOTHERAPEUTIC ACTIVITIES OF CARTHAMI FLOS AND ITS REVERSAL EFFECT ON MULTIDRUG RESISTANCE IN CANCER CELLS - Wu, Jimmy Yiu-Cheong; Yu, Zhi-Ling; Fong, Wang-Fun; Shi, Yi-Qian (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Multidrug-resistance (MDR) represents a major cause of failure in cancer chemotherapy. The need for a reduction in MDR by natural-product-based drugs of low toxicity led to the current investigation of applying medicinal herbs in future cancer adjuvant therapy. Carthami Flos (CF), the dried flower of safflower (Carthamus tinctorius L.), is one of the most popular traditional Chinese medicinal herbs used to alleviate pain, increase circulation, and reduce blood-stasis syndrome. The drug resistance index of the total extract of CF in MDR KB-V1 cells and its synergistic effects with other chemotherapeutic agents were studied. SRB cell viability assays were used to quantify growth inhibition after exposure to single drug and in combinations with other chemotherapeutic agents using the median effect principle. The combination indexes were then calculated according to the classic isobologram equation. The results revealed that CF showed a drug resistance index of 0.096. In combination with other chemotherapeutic agents, it enhanced their chemo-sensitivities by 2.8 to 4.0 folds and gave a general synergism in cytotoxic effect. These results indicate that CF could be a potential alternative adjuvant antitumour herbal medicine representing a promising approach to the treatment of some malignant and MDR cancers in the future.